2010
DOI: 10.1681/asn.2009101008
|View full text |Cite
|
Sign up to set email alerts
|

Racial Composition of Residential Areas Associates with Access to Pre-ESRD Nephrology Care

Abstract: Referral to a nephrologist before initiation of chronic dialysis occurs less frequently for blacks than whites, but the reasons for this disparity are incompletely understood. Here, we examined the contribution of racial composition by zip code on access and quality of nephrology care before initiation of renal replacement therapy (RRT). We retrospectively studied a cohort study of 92,000 white and black adults who initiated RRT in the United States between June 1, 2005, and October 5, 2006. The percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 45 publications
0
72
0
Order By: Relevance
“…15 Second, two separate studies have shown that patients who live in black majority communities or are treated in facilities located in such communities are significantly less likely to have received predialysis nephrology care. 16,17 No such data are available for other racial/ethnic groups. The need to ensure equitable access to home dialysis is even more urgent now as the use of both PD and home HD are seeing unprecedented and rapid growth, and these racial/ethnic differences need additional investigation.…”
Section: Discussionmentioning
confidence: 99%
“…15 Second, two separate studies have shown that patients who live in black majority communities or are treated in facilities located in such communities are significantly less likely to have received predialysis nephrology care. 16,17 No such data are available for other racial/ethnic groups. The need to ensure equitable access to home dialysis is even more urgent now as the use of both PD and home HD are seeing unprecedented and rapid growth, and these racial/ethnic differences need additional investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports suggest that sociodemographic differences may have important influences on chronic disease through mediators such as chronic stress, psychosocial factors (i.e., pessimism and low self-esteem), 21 acculturation, 22 environmental pollution, 23 or differences in access to care. 24,25 Whether or not these factors and their interaction with genetic predisposition may also explain race/ethnic differences in early kidney function decline will be an important area for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the receipt of nephrologist care is influenced by individual as well as contextual factors such as those related to residence, prior studies have mostly examined individual factors (12,(19)(20)(21), or the few studies that examined contextual factors have generally examined them separately (22)(23)(24) or were limited to certain regional areas (15,25). An important knowledge gap exists regarding broad regional (e.g., state-level) differences in the utilization of nephrologist care among patients with CKD stages 4-5.…”
Section: Introductionmentioning
confidence: 99%